2023
DOI: 10.3390/en16114487
|View full text |Cite
|
Sign up to set email alerts
|

Business Models for Energy Community in the Aggregator Perspective: State of the Art and Research Gaps

Abstract: Distributed Energy Resources (DERs) are spreading under the pressure of climate change mitigation plans and the framework, recognized as the most suitable to exploit DER diffusion, is the Energy Community (EC). Understanding the role of energy companies, especially Aggregators, in this context, is still an open topic, as it is not clear how they can support members in the aggregation process and how they create value through their business. The aim of the study is therefore to revise whatever is currently pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Some limitations in the literature on the role of aggregators in energy communities were identified, mainly in researching incentives and measures to encourage the creation of aggregations [33]. The authors have also identified the need for more research regarding the sizing of energy communities.…”
Section: Research Gapsmentioning
confidence: 99%
“…Some limitations in the literature on the role of aggregators in energy communities were identified, mainly in researching incentives and measures to encourage the creation of aggregations [33]. The authors have also identified the need for more research regarding the sizing of energy communities.…”
Section: Research Gapsmentioning
confidence: 99%
“…The literature on DR and aggregator participation in electricity markets has shown that DR can be an effective tool for balancing supply and demand on the grid and that aggregators can play an important role in providing flexibility and balancing services [22][23][24][25][26]. Aggregators' business models have been thoroughly researched [27][28][29][30][31][32]. However, there are still gaps in our understanding of the opportunities and challenges for aggregators in different European markets, and how these markets are behaving in terms of prices [33][34][35].…”
Section: Literature Review Of Types Of Markets In Which Aggregators C...mentioning
confidence: 99%